Monitoring Real Time Tingkat Kebisingan Laboratorium Ship Power Plan Berbasis Internet of Things - Rinaldi, Aditya; Jatmiko, M. Anang (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Noise generally depends on the level of noise intensity and the length of exposure time. The influence of high intensity noise (above NAB) in engine room activities causes damage to the ears which can reduce hearing quality, both temporarily and permanently. Based on the problems above, it is deemed necessary to conduct research in the form of designing a monitoring system that is capable of detecting noise. In this research, the sensor used is the GY Max 4466 sound sensor to detect noise at 4 object points. The microcontroller used is an ESP WROOM-32 because it has 16 ADC pins which makes it possible to run more than one analog sensor. Before use, the sensor will be tested with the aim of finding out the sensitivity of the sensor that will be used as a monitoring system tool. This noise monitoring system is carried out in real time based on the Internet of Things so that it will be easier to monitor directly to support work health and safety data. Through graphic analysis and comparison tables of accuracy values ​​above, information is obtained that the GY Max 4466 sensor has a very high level of accuracy to be able to provide information on noise levels in the ship power plan laboratory at the Jakarta College of Maritime Science. This is given by the percentage value of the accuracy of the measuring instrument made. exceeds 90% or has a coefficient of determination R2 value close to 1.